LiNuSR: impak pengurusan bilik darjah di sekolah kebangsaan - Isa, Anniliza Mohd; Mydin, Al-Amin; Abdullah, Abdul Ghani Kanesan (Universiti Malaya, 2021)
LiNuSR is the acronym for primary school literacy and numeracy related programs in Malaysia such as LINUS, LINUS 2.0 and PLaN conducted to ensure literacy and numeracy achievement is 100% after three years of study in primary school. The implementation of LiNuSR is generally carried out through classroom learning. Thus, this study was conducted to examine the influence of classroom management on LiNuSR. Another purpose was to look into the level of LiNuSR and classroom management, differences based on gender, teaching experience, school location and subjects as well as the relationship between the two variables. This study was conducted using a quantitative approach with surveys as a data collection technique. A total of 115 respondent consisting of level one teachers that teach Malay, Mathematics and English in the district of Sandakan, Sabah were selected through simple random sampling. Collected data were analyzed using SPSS version 25.0. The results show that both variables are at a high level. Only English subjects showed significant differences in classroom management compared to gender, teaching experience and location. There is a strong positive linear relationship between LiNuSR and classroom management and classroom management influenced 53.2% of the variance in LiNuSR. In addition to the findings of the study, the LiNuSR integration model - classroom management is proposed as a contribution to the field of study.